Pronationswinkel des Hinterfußes während Laufens in Bezug zur Belastung - Fromme, A.; Winkelmann, F.; Thorwesten, L.; Reer, R.; Jerosch, J. (Sportverletzung Sportschaden, 1997)
In 20 volunteers the relationship between rear-foot pronation and increasing physical exertion during treadmill ergometry was examined. In order to assess the influence of regularly performed running training a group of 10 endurance trained middle- and long-distance runners (age: 27.4 +/- 4.9 years; weight: 71.0 +/- 8.8 kg; height: 184.2 +/- 8.3 cm) was compared to another group of 10 untrained subjects (age: 24.7 +/- 2.1 years; weight: 73.3 +/- 9.8 kg; height: 179.1 +/- 8.3 cm). The examinations were carried out on a treadmill using a high-frequency motion analyzing system. Heart rate, blood lactate as well as rear-foot pronation were measured. Regarding heart rate and lactate concentration there were significant differences between trained and untrained volunteers. The pronation angle increased with higher speed up to a maximum of 6.54 +/- 4.22 degree for the trained group and 6.84 +/- 4.59 degree for the untrained group. With reference to maximal as well as submaximal stages the pronation angles showed no significant differences between both groups. Following the maximal exercise level the runners performed an additional 3 min run with a velocity reduced by 8 km/h compared to the maximal speed. At this level the total group as well as the untrained group showed significantly greater pronation angles compared to those of the corresponding velocity at the beginning of the test. The extent of the differences, however, was not significantly correlated with the lactate levels. Our results demonstrate that the increase of the pronation angle is a function of the running speed. But there is also an influence of fatigue, which depends neither on the running velocity nor on the lactate levels during exercise. Therefore, further investigations should emphasize the question which factors are responsible for this effect.